The Effect of Ginger and Lemon Aromatherapy on Nausea and Vomiting among Pregnant Women - Kustriyanti, Dwi; Putri, Arista Adityasari (Jurusan Keperawatan FIKES UNSOED, 2019)
Nausea and vomiting of pregnancy (NVP) are amongst the most common complaints of women during pregnancy, up to 80% of women have experienced various degrees of it. NVP impact on the quality of life, social and general well-being. The aim of this study was to determine the effect of ginger and lemon aromatherapy on nausea and vomiting of pregnancy (NVP). This study was randomized control trial in which 90 pregnant women with nausea and vomiting before 16 age gestation who had eligibility criteria. They were randomly divided into ginger, lemon and placebo groups. Women were asked to record their nausea and vomiting for 7 days by form of PUQE-24, in first three days they were advised to adjust their diet and then received aromatherapy for four days. Data were analyzed by ANOVA, Kruskal Wallis, Chi Square and Wilcoxon test. PUQE total scores before and after intervention in the ginger, lemon and placebo groups were 7.67 ± 2.304 vs. 6.85 ± 1.575, P = 0.000; 7.16 ± 1.598 vs. 5.50 ± 1.448, P = 0.000 and 6.70 ± 1.787 vs 5.50 ± 1.803, P value 0.00. Ginger and lemon essential oil were equally effective in reducing pregnancy nausea and vomiting.